A Campanha Nacional de Educação de Adultos no Estado Novo : uma leitura dos debates parlamentares - Silva, Daniela Vilaverde e (História: revista da Faculdade de Letras da Universidade do Porto, 2017)
The National Campaign for Adult Education (CNEA) and the Popular Education Plan developed in the New State represented educational initiatives that marked the decade of 50. This article aims to interpret sociologically the deputy speeches about the CNEA present on the parliamentary debates of two Parliamentary Chambers of the New State: the National Assembly and the Corporate Council. In the foreground, using documentary analysis of the minutes of the parliamentary debates of the two chambers seek to quantify the frequency of the term “adult education” and then proceeded to a content analysis of parliamentary debates. In content analysis we chose to create six dimensions that allowed us to interpret this adult education initiative in the context of a dictatorial regime. Reflecting on the debates revealed that the CNEA was an important means of disseminating the ideals of the New State, with the subdued education to the imperatives of the system and away from humanist and emancipatory ideals.